Rekayasa Kebutuhan dengan Metode Pemodelan Berbasis Linguistik dan Ontologi pada Sistem Penilaian Prestasi Kerja Pegawai Dinas Kominfo Kota Malang - Nurwida Mariatul Sadila; Fajar Pradana; Bayu Priyambadha (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Software requirements engineering is crucial in the software engineering process. One of the main causes of software requirements engineering failure is that the stages are not done quite well. The structuring and clearly defined semantic will make the requirement spesification easy to be understood and validated. Linguistic based modeling method and ontology be used for modeling specification and its validation base. Sistem Penilaian Prestasi Kerja Dinas Kominfo Kota Malang is used as case study in this thesis. The requirement specification which is obtained in the development process is modified and modeled into semantic model. DITA (Darwin Information Typing Achitecture) is used as semantic method which work for documenting the requirements in scenario format with additional ontology annotations. The additional ontology function is to be the reference from DITA to ontology or vice versa. It aims to facilitate the requirements understanding during the maintenance process. The requirements validation and verification is using the ontology method by applying the query to the requirements. The query results show the completeness, consistency, and correctness status toward the requirements. The benefits of performing the validation and verification to the requirements using this method are the requirements which have errors can be detected very soon and easily with the level of completeness, consistency, and correctness up to 100%.